EXPERIMENTAL CARDIOVASCULAR AND LUNG RESEARCHEvaluation of the impact of radical tumor resection in lung cancer patients on the activity of selected antioxidant enzymes - Misiak, Piotr; Rzepkowska-Misiak, Beata; Wcisło, Szymon; Dziwińska, Katarzyna; Malinowska, Katarzyna; Majsterek, Ireneusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : Oxidative stress appears to play an essential role as a secondary messenger in such physiological processes as apoptosis and survival as well as in proliferative signaling pathways. Oxidative damage is also considered to play a pivotal role in ageing, several degenerative diseases, and carcinogenesis. Lung cancer is the most common type of cancer, resulting in over 1.3 million deaths each year worldwide. Aim : The aim of this study was to evaluate the activity of selected antioxidative enzymes in patients with lung cancer before and after radical surgery. Material and methods : The study included 20 patients in the study group and 10 healthy volunteers in the control group. In the study group, blood samples were collected twice: one day before and one day after the operation. In the control group, blood samples were collected once. We estimated the activity of catalase (CAT), glutathione peroxidase (GPX), and superoxide dismutase (SOD) in erythrocytes. The total antioxidant status in blood plasma was also determined. Results : The activity of the selected antioxidative enzymes was greater in the case of GPX and CAT after surgery; the results were statistically significant in the study group. The activity of SOD remained at a comparable level. The total antioxidant status also increased after surgery in the study group in comparison to its preoperative level.